IMPLEMENTASI PERDA KOTA BENGKULU NOMOR 07 TAHUN 2013 TENTANG RETRIBUSI PELAYANAN PASAR (Studi Pada Pedagang Pasar Minggu Bertingkat) - Yuliana, Nurma (Jurnal Governance dan Administrasi Publik, 2018)
The purpose of this research is to know the implementation of the Government of Bengkulu number 07 year 2013 about the retribution of market services (study on the Pasar Minggu Kota Bertingkat). In this research researchers use descriptive qualitative to describe the phenomena that exist and take place today. The focus of this research on implementing the Perda of Bengkulu City number 07 year 2013 concerning the retribution of market service. The research aspect is, object and subject of retribution, tariff of retribution, way of voting, territory of voting, period of retribution and the time of outstanding retribution and administrative sanction. Data analysis technique is data reduction, data display and conclusion. The results of the research of the implementation of the city of Bengkulu on the retribution of market services found in the field that there is still the tariff imposed/paid to the collector does not match the existing facility leasing data on Perda and UPTD data and Dinas Perindag, other than that there are still traders who do not know the breadth of facilities they use. And the procedure of payment and voting are still merchants and collectors who do not use media/card subscriptions. It was concluded that regulation of the city of Bengkulu No. 07 year 2013 about the retribution of market services applied in Pasar Minggu Kota Bengkulu is still not implemented or well implemented according to the regulations that have been made by the local government.